De que família cuida a saúde da família? Os efeitos de poder nas relações de cuidado entre equipe e famílias - Ferreira, Luis Henrique Moura (2014)
This study adopted the Family Health Strategy (FHS) as the locus of research. The FHS is the Brazilian government's response to the organization and execution of Basic Health Care. Analyzes the FHS as a strategical dispositive in the art of governing the population wich adopts the family as a central instrument for developing epidemiological changes, based on the concept of Governamentality, an exercise of power inserted in the relationship between security, population and government. Some effects of this power are normalization of conduct, medicalization of life, imposing lifestyles considered healthy from political technologies that investing on the body, health, the right ways to eat, to live and interact, in sume an entire space of existence. This work has taken as its object FHS care practices, analyzing how they can determine the ways of life and subjectivity of families who receive assistance, for it adopted the theoretical framework of analytical power of Michel Foucaut. From the perspective of Social Constructionism, were analyzed official documents from the Ministry of Health and observed the daily work of a family health team, analyzing the discursive practices in these different fields of research. The process of this investigation resulted in the possibility to analyze and relate the meanings of three discursive practices: Families, Power and Care. In the documentary analysis, three groups of meaning were discussed: (1) as the FHS healthcare model approaches of a Governmentality dispositive; (2) the meanings of family treated in the documents, the highlight occurs in the created norms on families, and as this is an important strategy for the good government of the population; (3) the strategic position that discursive practices of Care and Humanization occupy in the documents and the changes they propel to care practices. In participant observation, we report three situations experienced in the field, it is argued from these reports the main meanings of team care concrete practices and the effects of power in families. In the final considerations discusses the three discursive practices that made up this work: Power, Families and Care, tracing possible ways that contribute to the movement of Clinical and Care Management, and indicating FHS care practices in order to enable a ethical and humane meeting between worker-user which generates autonomy, emancipation growth for these different actors.